Cystatin C as Marker for Detection of Renal Function Change in Obstructive Uropathy Due to Ureteric Stone - Mufeed J. Ewadh (Journal of Global Pharma Technology, 2018)
Objective: To Detection of Ureteric Stone Using Cystatin C "marker in Compare with serum Creatinine. Methods: Between September 2016 to February 2017 at Al-Hilla Teaching Hospital, Urology Department. The study group consisted of 25 healthy subjects as control with age between (20-66)year and 25 patients of Ureteric Stone with age from (20-62)year, the biochemical measurement including human CST3 (Cystatin C), ELISA kit used in the present study and serum Creatinine test used as biochemical diagnostic assessment. Results: Statistical analysis show significant difference (P<0.005) in the mean age (40.64±11.47), 21-30 years was the most influential of these disease compared with the other age groups. The percentages of males and females in patients group 16(64%) and 9(36%) respectively, while in the control group female were 14(56%), and male 11(44%) respectively. In total twenty five  patients  60% from the total  number  were unilateral and 40%  bilateral ureteric stone, study reveals that there was a significant increase (P. value<0.001) in the Cystatin C marker between study groups the mean value was (2.56 ±0.81) compared to  control group (0.82 ±0.17) with (P. value<0.001). Creatinine level revealed no significant association (p>0.05) between the level in the control and patients. In order to confirm the results of cystatin C levels using ELISA , the characteristic of the teqnique :Sensitivity (92%) , Specificity (96%).The characteristic of colorimetric methods test as compare to clinical diagnosis  in detection of Creatinine :Sensitivity (40%) , Specificity (88%). Conclusion: Cystatin C found to be a more accurate than Creatinine in detection the obstruction due to ureteric stone.Keywords: Creatinine, Stone, Cystatin C, Biochemical study, Urinary Tract.